Comparison of the efficacy of treatment with clobetasol propionate or bexarotene in early-stage mycosis fungoides - Aslı Aksu Çerman; Pinar Ozdemir Cetinkaya; Birgül Özkesici Kurt; Artun Kırker; İlknur Altunay (Anais Brasileiros de Dermatologia)
Abstract Background: There are few studies in the literature comparing the effectiveness of topical treatments in early-stage mycosis fungoides (MF). Objectives: It was aimed to evaluate the clinical efficacy, side effects and topical treatment compliance with bexarotene or clobetasol propionate in early-stage MF. Methods: A total of 40 patients with stage IA-IB MF were enrolled in the study. Twenty patients were treated with 1% bexarotene gel and 20 patients were treated with 0.05% clobetasol propionate ointment. Results: In the bexarotene group, 11 patients (55%) had complete clinical response (CCR) and 5 patients (25%) had partial response (PR) while in the clobetasol propionate group, 10 patients (50%) had CCR and 9 patients (45%) had PR. The median duration of remission was 10.5 months in the bexarotene group and 4 months in the clobetasol propionate group. The remission period was statistically significantly longer in the bexarotene group (p = 0.032). Irritation symptoms were statistically significantly more common in the bexarotene group (p = 0.001). Study limitations: The limitation of the study was its retrospective design. Conclusion: Both topical bexarotene and topical clobetasol propionate were found to be effective in MF. Irritation symptoms were more common with topical bexarotene. Moreover, the remission period with topical bexarotene was significantly longer.